RADICALISING THE TRADITIONALISTS - Ahmad Zainul Hamdi (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
The post-New Order Indonesian politics has provided a political opportunity structure for the state towards democratization. It has a double-edged sword: on the one hand democratization could lead to the civic engagement, but on the other hand, it provides a hot bed for the flourishing of anti-civic organization. As for the latter, following the fall of authoritarian regime of new Order in 1998, Indonesians have also witnessed the birth of transnational Islamist and radical organizations threatening the state’s integrity and peaceful coexistence of the citizens. Amid the public appearance of these radical organization, an issue of ideological infiltration and sabotage of radical organization upon mainstreaming moderate Muslim organizations, such as Nahdlatul Ulama and Muhammadiyah do exist. This article tries to reveal the impacts of a such infiltration practices and the extent that radical narratives win the minds and hearts of important Muslim leaders. Taking a closer a look to Muslim leaders in Sampang district in the island of Madura, the centrum of traditionalist Muslim in Indonesian Islamo-landscape, the article finds out that intolerant and radical ideologies do resonate clearly among the leaders. This finding resort as an alarm and counter-narrative to the long-admired Islamic traditionalism as an important backbone for moderate Islam in Indonesia.